Synthesis and characterization of the first inhibitor of N-acylphosphatidylethanolamine phospholipase D (NAPE-PLD). Issue 95 (16th November 2017) - Castellani, Beatrice; Diamanti, Eleonora; Pizzirani, Daniela; Tardia, Piero; Maccesi, Martina; Realini, Natalia; Magotti, Paola; Garau, Gianpiero; Bakkum, Thomas; Rivara, Silvia; Mor, Marco; Piomelli, Daniele
Abstract : ARN19874 is a quinazolinedione sulfonamide derivative that inhibits NAPE-PLD, a membrane-associated enzyme that cleaves N -acylphosphatidylethanolamines (NAPEs) into fatty acid ethanolamides (FAEs). Abstract : N -Acylphosphatidylethanolamine phospholipase D (NAPE-PLD) is a membrane-associated zinc enzyme that catalyzes the hydrolysis of N -acylphosphatidylethanolamines (NAPEs) into fatty acid ethanolamides (FAEs). Here, we describe the identification of the first small-molecule NAPE-PLD inhibitor, the quinazoline sulfonamide derivative 2, 4-dioxo- N -[4-(4-pyridyl)phenyl]-1 H -quinazoline-6-sulfonamide, ARN19874.